2021
DOI: 10.3389/fnagi.2021.784356
|View full text |Cite
|
Sign up to set email alerts
|

The Locus Coeruleus Noradrenaline System in Delirium

Abstract: Delirium is a brain state involving severe brain dysfunction affecting cognitive and attentional capacities. Our opinion statement review aims to elucidate the relationship between abnormal arousal and locus coeruleus (LC) activity in cognitive dysfunction and inattention in delirium states. We propose (1) that enhanced noradrenaline release caused by altered arousal in hyperactive delirium states leads to increased noradrenergic transmission within the LC and subcortical and cortical brain regions including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Gao et al demonstrated that transcutaneous electrical acupoint stimulation at bilateral LI4 and PC6 reduced neuroinflammation by lowering the permeability of the blood-brain barrier ( 12 ). Studies reported that one potential mechanism by which auricular acupressure may exert its anti-delirium effect is activating the locus coeruleus noradrenergic system, which is one of the central vagal relay centers and plays a critical role in the generating and regulating of delirium ( 27 , 28 ). By stimulating the ear branch of the vagus nerve, auricular acupressure may exert an add-on neuroprotective effect by direct and indirect modulation of the activity and connectivity of the locus coeruleus noradrenergic system, thus modulating the release and uptake of noradrenaline and dopamine in some key brain regions, including the prefrontal cortex and hippocampus, which are postulated to be associated with attention, memory, and other cognitive dysfunction ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al demonstrated that transcutaneous electrical acupoint stimulation at bilateral LI4 and PC6 reduced neuroinflammation by lowering the permeability of the blood-brain barrier ( 12 ). Studies reported that one potential mechanism by which auricular acupressure may exert its anti-delirium effect is activating the locus coeruleus noradrenergic system, which is one of the central vagal relay centers and plays a critical role in the generating and regulating of delirium ( 27 , 28 ). By stimulating the ear branch of the vagus nerve, auricular acupressure may exert an add-on neuroprotective effect by direct and indirect modulation of the activity and connectivity of the locus coeruleus noradrenergic system, thus modulating the release and uptake of noradrenaline and dopamine in some key brain regions, including the prefrontal cortex and hippocampus, which are postulated to be associated with attention, memory, and other cognitive dysfunction ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that one potential mechanism by which auricular acupressure may exert its anti-delirium effect is activating the locus coeruleus noradrenergic system, which is one of the central vagal relay centers and plays a critical role in the generating and regulating of delirium ( 27 , 28 ). By stimulating the ear branch of the vagus nerve, auricular acupressure may exert an add-on neuroprotective effect by direct and indirect modulation of the activity and connectivity of the locus coeruleus noradrenergic system, thus modulating the release and uptake of noradrenaline and dopamine in some key brain regions, including the prefrontal cortex and hippocampus, which are postulated to be associated with attention, memory, and other cognitive dysfunction ( 27 29 ). As postoperative delirium has been speculated to be a harbinger for postoperative cognitive dysfunction, the mechanism of acupuncture to prevent postoperative delirium may be similar to those of acupuncture to prevent postoperative cognitive dysfunction, which is by attenuating systemic inflammation and neuroinflammation, reducing oxidative stress levels, improving synaptic plasticity, and reducing neuronal injury ( 10 , 12 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another acupuncture technique, auricular acupressure, has been reported to exert its neuroprotective and anti-delirium effects by stimulating the auricular branches of the vagus nerve and activating the noradrenergic system of locus locus, one of the central relay centers of the vagus nerve, which plays a key role in the generating and regulation of delirium. [ 43 , 44 ] By directly or indirectly regulating the activity and connectivity of the norepinephrine system in locus locus, auricular acupressure regulates the release and uptake of norepinephrine and dopamine in some key brain regions, including the prefrontal cortex and hippocampus, which are postulated to be associated with attention, memory, and other cognitive dysfunction. [ 45 ] A review article by Hou et al [ 46 ] is consistent with the above views, showing that auricular acupressure can relieve pain, treat insomnia and anxiety, and improve sleep quality, and its mechanism may be achieved by regulating the neuroendocrine system, neuroinflammation and neural reflex, as well as antioxidant effects.…”
Section: Potential Mechanisms Of Acupuncture Against Podmentioning
confidence: 99%
“…These agents exert their therapeutic effects by modulating alpha-2A, 2B, and 2C receptors and subsequently inhibit the presynaptic release of norepinephrine (NE) [ 8 , 9 ]. Delirium models have supported an excess of NE, which propagates neuronal damage and cell death, thus worsening symptomatology [ 14 , 18 ]. Additionally, these alpha-2 agonists may inhibit glutamate release via the suppression of voltage-dependent calcium channels and mitogen-activated protein kinase [ 19 ].…”
Section: Introductionmentioning
confidence: 99%